1999
DOI: 10.2337/diabetes.48.9.1754
|View full text |Cite
|
Sign up to set email alerts
|

A defect late in stimulus-secretion coupling impairs insulin secretion in Goto-Kakizaki diabetic rats.

Abstract: A widely accepted genetically determined rodent model for human type 2 diabetes is the Goto-Kakizaki (GK) rat; however, the lesion(s) in the pancreatic islets of these rats has not been identified. Herein, intact islets from GK rats (aged 8-14 weeks) were studied, both immediately after isolation and after 18 h in tissue culture. Despite intact contents of insulin and protein, GK islets had markedly deficient insulin release in response to glucose, as well as to pure mitochondrial fuels or a non-nutrient membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
41
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 53 publications
10
41
2
Order By: Relevance
“…These phenotypic data are in agreement with those published by Cohen et al (27) in earlier studies, in which they showed in CDs rats that were fed HSD for Ͼ2 months a moderate fasting hyperinsulinemia and a subsequent agedependent reduction in their ability to secrete insulin in response to glucose stimulation. A similar impaired insulin response also has been described in GK rats (7,28). A possible explanation for these findings is prolonged exposure to hyperglycemia per se, which exhausts the insulinsecreting ability of the pancreas (13,17,18,28 -31).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These phenotypic data are in agreement with those published by Cohen et al (27) in earlier studies, in which they showed in CDs rats that were fed HSD for Ͼ2 months a moderate fasting hyperinsulinemia and a subsequent agedependent reduction in their ability to secrete insulin in response to glucose stimulation. A similar impaired insulin response also has been described in GK rats (7,28). A possible explanation for these findings is prolonged exposure to hyperglycemia per se, which exhausts the insulinsecreting ability of the pancreas (13,17,18,28 -31).…”
Section: Discussionmentioning
confidence: 61%
“…Its most outstanding and distinctive feature is that it expresses genetic susceptibility (sensitivity and resistance) to a carbohydrate-rich diet, a central feature of type 2 diabetes in humans (1,2,4,5) that is not present in other major genetically inbred rat strains that simulate type 2 diabetes in humans. The other major rat models of type 2 diabetes, the Goto-Kakizaki (GK) (6,7), the Otsuka Long-Evens Tokushima Fatty (OLETF) (8 -10), and the Zucker diabetic fatty (ZDF) rats (11,12) develop diabetes spontaneously, without any important relationship to the composition of diet. Another central feature of the Cohen model is that it consists of two genetically derived contrasting strains, originating from the same parent strain, which is useful for genetic and physiological studies.…”
mentioning
confidence: 99%
“…However, in previous investigations involving 8-week-old Wistar, GK and hybrid rats from the Stockholm colony, a majority of the islets appeared histologically normal and only a few starfishshaped islets were found (Abdel-Halim et al 1994, Guenifi et al 1995. In other studies, no differences in islet -cell density or insulin content were seen between GK rats and Wistar rats at 12 weeks of age (Ohneda et al 1993, Höög et al 1996, Metz et al 1999. The animals studied in the present experiments were 14 weeks old, and were thus not expected to show significant aberrations in islet architecture or -cell mass.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, treatment of GK rats with nateglinide, an insulin secretagogue, reduces postprandial hyperglycemia and elicits early-phase insulin secretion, a phenomenon not observed in type 1 diabetes (26,27). Insulin resistance and hyperlipidemia often accompany type 2 diabetes, and the presence of these risk factors in GK rats has been controversial (22,28,29). Thus, we specifically assessed the presence of these risk factors in our colony.…”
Section: Discussionmentioning
confidence: 99%